?-Statistical Derivative - Idris, Samar; Colak, Rifat (Springer-Verlag Singapore Pte Ltd, 2024)
This investigation article concentrates on de ning lambda-statistical derivative, (V, lambda)-statistical derivative, and strong (V, lambda)-statistical derivative using statistical and Ces ro derivatives. Established on the rst concept, we examine the a nity between statistical and ordinary derivatives. Furthermore, we de ned (V,lambda)-continuity and studied the relationship between it and (V, lambda)-derivative. The connection between lambda-statistical derivative and strong (V,.)-statistical derivative has been discussed too. Finally, we examined the a nity between strong. (V,mu)-statistical derivative and strong (V, lambda)-statistical derivative, under some conditions, for any lambda, mu in Lambda.
10th International Conference on Mathematics and Computing-ICMC -- JAN 02-07, 2024 -- INDIA
Keywords: Statistical derivative; l-statistical derivative; (V,lambda)-statistical derivative; Strong (V, lambda)-statistical derivative